Unsaturated Polyester Resins : Fundamentals, Design, Fabrication, and Applications - Thomas, Sabu (Elsevier, 2019)
Unsaturated Polyester Resins: Fundamentals, Design, Fabrication, and Applications explains the preparation, techniques and applications relating to the use of unsaturated polyester resin systems for blends, interpenetrating polymer networks (IPNs), gels, composites and nanocomposites, enabling readers to understand and utilize the improved material properties that UPRs facilitate. Chapters cover unsaturated polyester resins and their interaction at the macro, micro and nano levels, in-depth studies on the properties and analysis of UPR based materials, and the applications of UPR based composites, blends, IPNs and gels across a range of advanced commercial and industrial fields. This is a highly detailed source of information on unsaturated polyester resins, supporting academics, researchers and postgraduate students working with UPRs, polyesters, polymeric or composite materials, polymer chemistry, polymer physics, and materials science, as well as scientists, R & D professionals and engineers in industry.
Keywords: Polyesters.; Gums and resins, Synthetic.; elektronické knihy; electronic books